Childhood poisoning in Warri, Niger Delta, Nigeria: A ten year retrospective study - Gilbert I.M. Ugwu (African Journal of Primary Health Care & Family Medicine, 2012)
Background: Childhood poisoning is a common but avoidable problem in developing countries such as Nigeria. Objectives: To determine the pattern of childhood poisoning in the Warri Niger Delta Region of Nigeria.